Literasi Politik di Desa: Suatu Upaya Pencegahan Politik Uang Dalam Menghadapi Pemilu 2024 - Hartomi Akta Padma Eldo, Dwian; Abdurochman, Latif; Fahrulrozi, Rifqi; Meilina, Meilina (COVIT (Community Service of Tambusai), 2023)
Money politics is one of the damaging factors in the life of democracy in Indonesia. This community service aims to provide education in the form of political literacy about the dangers of money politics that often occur during elections. Money politics has a negative impact in Indonesia, including eliminating community sovereignty, distorting democracy, and worsening the quality of democracy itself. Therefore, a joint commitment is needed to fight money politics, especially in villages where money politics often occurs. The method used in this community service is to conduct intense lectures to the Perboto Village Community of Wonosobo Regency about the dangers and impacts of money politics. The findings of the community service show that money politics still often occurs at the existing election levels, both from the presidential election, governor, regent, and even village head elections. Therefore, this socialization activity is beneficial for the Perboto Village Community, Wonosobo Regency in adding insight into the dangers of money politics, which can also impact themselves and not only affect the person who gives. In addition, Indonesia will also face simultaneous elections in 2024, which is a good enough reason to increase socialization about the dangers of money politics in the community. Keywords: Political Literacy, Money Politics, Village People, 2024 general election